A novel coaxial focus position detection technique based on differential modulation evaluation for laser direct photolithography. (February 2023) - Han, Chenhaolei; Tang, Yan; Cheng, Xiaolong; Sun, Haifeng; Feng, Jinhua; Hu, Song
Highlights: A novel coaxial focus position detection technique based on differential modulation evaluation is proposed for improving focus position detection accuracy. The proposed method can eliminate the influence of different reflectivity of the surface of the substrate. Through experimentally verified, the focus detection accuracy is better than 5nm in the case of an objective lens with a numerical aperture of 0.9. Abstract: In laser direct lithography, coaxial focus position detection techniques are needed to ensure the manufacturing accuracy. The existing coaxial focus position detection techniques include pinhole method, critical angle method, Foucault knife-edge method and astigmatism method, which are susceptible to the intensity fluctuation and have high requirement for the installation and adjustment of the system. Furthermore, the resolution of existing method is generally between 10-20nm. We proposed a novel coaxial focus position detection technique based on differential modulation evaluation. In this study, the imaging space of the lithography lens is coded by grating pattern. And a differential detection system is used to get the substrate height from the image modulated by the lens focus depth. Moreover, this proposed method can eliminate the influence of different reflectivity of the surface of the substrate. Furthermore, the focus detection accuracy is better than 5nm in the case of an objective lens with a numerical aperture of 0.9.